Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Some pre algebra help

  1. May 24, 2006 #1
    could some one help me fine the products with these problems.


    -3x3(2x3 +3x-4)
     
  2. jcsd
  3. May 24, 2006 #2
    the little 3s mean to the third power
     
  4. May 24, 2006 #3
    x1=x2=x3=0
    x4=0.879615
    x5= -0.439807 + i 1.44232
    x6= -0.439807 - i 1.44232

    I found arithmetically. I hope I'm right
     
  5. May 24, 2006 #4
    I am pretty sure that is not the right answer
     
  6. May 24, 2006 #5
    here are 2 others
    1. (x+1)(x-2)


    2.(4x-2)(-x+3)
     
  7. May 24, 2006 #6
    I've just checked my answers and they are absolutely right.
    Unless you are not asking for the solution of the
    -3(x^3) ( 2(x^3) + 3x - 4) = 0
    What you've written (about the 2 others) has nothing to do.
     
  8. May 24, 2006 #7
    i need to find the product of

    1. (x+1)(x-2)


    2.(4x-2)(-x+3)
     
  9. May 24, 2006 #8
    nvm i figured it out
     
  10. May 24, 2006 #9
    (x+1)(x-2) = (x^2) -x -2 = 0 -> x1= 2
    and x2= -1

    (4x-2)(-x+3) = -4(x^2) +14x -6 =0 -> x1 = 3
    and x2 = 0.5

    But again, it has nothing to do with the first one.
     
  11. May 24, 2006 #10
    Stop assuming what is being posted are equations because they are not. Do you see an equal sign in any of the above posts exclusing your own? The OP has posted expressions asking for help in expanding them, there is nothing to solve for since there is no equation at all.
     
  12. May 24, 2006 #11
    (Homework help should be posted in the homework help forums)
     
  13. May 25, 2006 #12
    Ok I'm sorry. Stop shooting! The problem is with my english.
     
  14. May 25, 2006 #13

    HallsofIvy

    User Avatar
    Staff Emeritus
    Science Advisor

    "=" has nothing to do with "English"!
     
  15. May 28, 2006 #14
    I thought products meant roots.
     
  16. May 28, 2006 #15
    Again, you're right. I 'm sorry.
     
  17. May 28, 2006 #16
    ^ means to the power of.
    Is this right?

    -3x^3(2x^3 +3x-4) = -6x^6 - 9x^4 + 12x^3

    (x+1)(x-2) = x^2 + x - 2x -2 = x^2 - x - 2

    (4x-2)(-x+3) = -4x^2 + 2x + 12x - 6 = -4x^2 + 14x - 6
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?